55.5k views
2 votes
Please show all work and not just the answers.

Please show all work and not just the answers.-example-1
User Davion
by
5.7k points

2 Answers

7 votes

Answer:

√113

Explanation:

B(3,5) , A(-4,-3)

distance between 2 points : d

d=√(x2-x1)²+(y2-y1)²

d=√(3-(-4)²+(5-(-3)²

d=√7²+8²

d=√49+64

d=√113

User PopKernel
by
5.7k points
7 votes

Answer:

√113

Explanation:

As per distance formula:

  • d =
    √((x2-x1)^2 + (y2-y1)^2)

Points are:

  • A(-4, -3) and B(3,5)

So the distance:

  • d =
    √((3+4)^2 + (5+3)^2) =
    √(7^2 + 8^2) =
    √(49+64) = √(113)

Answer is √113

User Largato
by
5.3k points